Design and Development of Bikes-Spoke Guard (BSG) - Anuar, Muhammad Hasif; Jamian, Rahim (Progress in Engineering Application and Technology, 2021)
Motorcycle is an essential mode of transportation in many countries. In recent years, there are increasing trend of accident involving motorcyclist, which concerning to spoke injury. This research study was attempted to develop a prototype model of bike-spoke guard (BSG) in preventing the spoke injury. The proposed design was based on a comprehensive literature and industrial pattern search to suit with the design specification of underbone type of motorcycle. The design employed polyester resin as main material. The analysis method involved failure modes and effects analysis (FMEA) and finite element analysis (FEA). Based on FMEA results, the risk of passenger’s feet trap on bikes spoke was considered high priority. The result of FEA by means of stress and displacement ascertained the computer-aided design (CAD) model of BSG could withstand weight of passenger up to 150 kg. The findings revealed the proposed model could enhance the design and safety performance of the existing spoke protective device toward reducing the spoke injury. Recommendations are also highlighted including fabrication process, functional test and variety of design for the further development of BSG.